O método combinativo entre analogia e imaginação na obra crítica da razão pura do filósofo alemão Immanuel Kant - Freire, Hálwaro Carvalho (2019)
This research investigates the relationship between the "concept" of analogy and the faculty of imagination in the Critical Pure Reason work by the German philosopher Immanuel Kant. This research seeks to show the connections between analogy and imagination, against the background of synthesis and time. First, we seek to understand exactly what is the synthetic function of the faculty of imagination in dialogue with CRP Transcendental Deduction A and B. With this, we work the synthetic functions (apprehension, reproduction and recognition) as the first part of the link between the faculty of sensibility and the faculty of understanding. Moreover, the procedure adopted also includes analyzing the relationship between the chapter of Transcendental Schematism and the Pure Principles of Understanding, specifically the Analogies of experience, as a second part of the link between sensitive representations and conceptual representations. Following the analysis of these chapters, we suggest a combinatory method between analogy and imagination as a credential or alternative to the debate between conceptualists and non-conceptualists regarding the relations of intuitions and concepts in the aforementioned work. Thus, we argue, ultimately, that the combinatory method between analogy and imagination safeguards the fundamental elements (synthesis and time) for the association between intuitions and concepts.